Water Corrosion and Scale Formation Problem and Its Solution in Water Supply Schemes – A Case Study on Padampokhari and Mahendranagar Scheme - Panday, Hari Prasad; Khanal, S.N.; Khatiwada, N. R.; Adhikari, Bikash (Kathmandu University Journal of Science Engineering and Technology, 2021)
The water with low total dissolved solid (TDS) and pH value is corrosive in nature. Moreover, the water with high TDS and low pH values is scale forming. A low TDS and pH value dissolves intake structures, GI pipes, concrete reservoir, household plumbing systems and cementing structures when it comes in contact with it. Furthermore, the corrosive water causes nuisance and health-related problems. Excess intake of lead, aluminum, copper, iron, chromium etc. in human body due to corrosive water causes serious damage to the different human organs such as brain, kidney, nervous system, blood cells, and even degrade an IQ level. High TDS and low pH value causes scale formation which blocks the whole water supply system. This paper presents a method for identification of corrosive and precipitative water and propose a solution to normalize it. The corrosive and scale forming water is detected easily by measuring a chief indicator parameter, TDS. The increasing value of TDS from intake to tap stand notifies that the water is corroding, and its decreasing values denotes the scale formation. Corrosive water is stabilized using calcium carbonate stones which is easily available in nature. On the other hand, scale forming water is controlled by the structural modifications of intake, collection tank, pipeline and reservoir etc. which we have constructed or going to construct. To verify the proposed methods, case study on Padampokhari and Mahendranager water supply schemes are studied and presented here in detail.